Silica nanochannels boosting Ru(bpy)32+-mediated electrochemical sensor for the detection of guanine in beer and pharmaceutical samples - Yang, Luoxing; Zhang, Tongtong; Zhou, Huaxu; Yan, Fei; Liu, Yan (Frontiers in Nutrition, 2022)
Vertically-ordered mesoporous silica film (VMSF) with uniform mesoporous channels perpendicular to electrode substrate has a wide range of applications in direct electroanalysis of complex samples. However, detection of nucleic acid bases is difficult to realize at the commonly used VMSF modified indium tin oxide (VMSF/ITO) electrode due to the high overpotentials of underlying ITO for many small organic molecules. In this work, we demonstrated an electrochemical method for sensitive detection of guanine (G) by integration of VMSF/ITO and tris(2,2′-bipyridine) ruthenium (II) (Ru(bpy)32+) redox mediator. Ru(bpy)32+ electrostatically accumulated by VMSF is able to act as an electron shuttle between G and underlying ITO surface, showing electrocatalytic oxidation of G and enabling the quantitative determination of G with a limit of detection (LOD) of 0.058 μM and a limit of quantitation (LOQ) of 0.2 μM. Electrochemical detection performance for G could be regulated by changing the pH of supporting electrolyte and the content of Ru(bpy)32+, achieving a wide dynamic linear range from 0.2–10 μM (R2 = 0.999), 2–100 μM (R2 = 0.999) and 10–500 μM (R2 = 0.998). Furthermore, owing to the good anti-fouling and anti-interference ability of VMSF, this simply sensing strategy can be applied to the direct and rapid detection of G in beer samples, and detection of ganciclovir (G analogue) content in ganciclovir eye drops.